Inhibition of Aurora Kinase A Synergistically Enhances Cytotoxicity in Ovarian Clear Cell Carcinoma Cell Lines Induced by Cisplatin: A Potential Treatment Strategy. Issue 8 (1st October 2017) - Chiba, Yohei; Sato, Seiya; Itamochi, Hiroaki; Yoshino, Naoto; Fukagawa, Daisuke; Kawamura, Hideki; Suga, Yasuko; Kojima-Chiba, Atsumi; Muraki, Yasushi; Sugai, Tamotsu; Sugiyama, Toru
Abstract : Objective: This study aims to clarify the incidence of Aurora kinase A (Aurora-A) protein expression and its correlation with clinical parameters in ovarian clear cell carcinoma (OCCC) tumor tissues. In addition, we assessed the efficacy of ENMD-2076, a novel selective Aurora-A inhibitor, in combination with chemotherapeutic agents for the treatment of OCCC. Methods/Materials: Aurora-A protein expression was determined by immunohistochemical staining of OCCC specimens from 56 patients to evaluate its correlation with clinical outcomes in OCCC. In the in vitro study, 6 OCCC cell lines were exposed to ENMD-2076 in combination with cisplatin, SN38, doxorubicin, or paclitaxel, and cell proliferation, cell cycle distribution, and apoptosis were assessed. Results: The 5-year survival rates of International Federation of Gynecology and Obstetrics stages IC3 to IV patients with intermediate or strong Aurora-A expression were significantly lower than those of patients with negative or weak Aurora-A expression. Increased Aurora-A expression was associated with significantly worse overall survival of International Federation of Gynecology and Obstetrics stages IC3 to IV patients (21% vs 77%). Multivariate analysis revealed that Aurora-A expression was an independent prognostic factor for stages IC3 to IV OCCC patients. Furthermore, synergistic effects were observed with ENMD-2076 in combination with cisplatin or SN-38 in 4 of the 6 tested cell lines. ENMD-2076 dramatically enhanced apoptosis and cell cycle arrest at the G2/M phase induced by cisplatin. Conclusions: Aurora-A is a promising biomarker that is predictive of patient outcomes and a potential target for OCCC. The results suggested that chemotherapy, including ENMD-2076 in combination with cisplatin, is a potential treatment modality for patients with OCCC.